Ideology versus Ethicality in the Enactment of Obamacare: Justice and Autonomy as Contested Issues - Mahboub, Oussama (Milev Journal of Research and Studies, 2021)
One of the most politically debatable issues in America is the reform of the healthcare sector. The heated dispute is conducted by liberals and conservatives. Accordingly, among the programs that helped divide the American ideological spectrums was the enactment and implementation of the Patient Protection and Affordable Care Act (ACA, Obamacare) in 2010. The law received unconditional acclaim by liberals and severe criticism from conservatives. The present paper attempts at analyzing both the impetus that lies behind the political division over the law and the conformity of the two ideological spectrums with major public health ethical principles including justice and the respect for persons' autonomy. Through taking Obamacare as a case study, this research uses the Metaphor Theory adopted by George Lakoff in order to trace the endeavor behind the liberal and conservative policies, and employs two key contested principles included in a relevant theory known as Principlism, namely justice and autonomy in an attempt to assess the extent of the liberals' and conservatives' compatibility with public health ethics. This study sums upwith the idea that the liberal moralists show more conformity to public health ethics highlighted by the justice and autonomy principles compared to their conservative counterparts.